A mixed-spin spin-crossover thiozolylimine [Fe4L6]8+ cage. Issue 27 (14th June 2019) - Li, Li; Craze, Alexander R.; Mustonen, Outi; Zenno, Hikaru; Whittaker, Jacob J.; Hayami, Shinya; Lindoy, Leonard F.; Marjo, Christopher E.; Clegg, Jack K.; Aldrich-Wright, Janice R.; Li, Feng
Abstract : A mixed-spin spin-crossover thiozolylimine [Fe4 L6 ] 8+ tetrahedral cage is reported. Abstract : The self-assembly of a mixed-spin [Fe4 L6 ] 8+ tetrahedral cage is reported. The cage undergoes temperature induced spin-crossover with a 29 K hystereisis. Variable temperature X-ray photoelectron spectroscopy (VT-XPS), combined with SQUID data, allowed differentiation between the surface and bulk magnetic properties.